Parasites of the ‘‘Peladilla", Aplochiton zebra (Osmeriformes: Galaxiidae), from Patagonia (Argentina and Chile) - Fernández, María Valeria (2012)
Aplochiton zebra is found inhabiting lakes and rivers in Patagonia (Chile and Argentina) and the Malvinas Islands (Falklands Islands). The peladilla is not commercially fished; thus, not much is known about its biology. In previous studies, 7 parasite species were recorded from this fish species. The aim of the present work is to provide new data of A. zebra parasites from surveys in Argentinean Patagonia and to compile the published information from Argentina and Chile. A total of 217 A. zebra from 5 lakes were collected and 15 parasite species were found: 2 Protozoa, 1 Myxozoa, 6 Digenea, 1 Cestoda, 1 Acanthocephala, 3 Nematoda, and 1 Mollusca. This checklist contributes 11 new records of parasites from A. zebra.